Odpowiedź :
Odpowiedź:
5.
a) 2*3x+2*(x+6)=60
b) 8*(2x-1)=56
6.
a) 2x-1=4x+2
2x-4x=1+2
-2x=3 |:(-2)
x=-2/3
b) [tex]\frac{3x+1}{5} =x+3[/tex]
3x+1=5x+15
3x-5x=15-1
-2x=14 |:(-2)
x=-7
7. 2(x+1)+6=4(2-3x)-4
2x+2+6=8-12x-4
2x+12x=-2-6+8-4
14x=-4 |:14
x=-4/14
x=-2/7
8.
3(x+1)-2=4x+5
3x+3-2=4x+5
3x-4x=-3+2+5
-x=4 |:(-1)
x=-4
Szczegółowe wyjaśnienie:
Odpowiedź:
zad. 5
a) x+6+3x+x+6+3x= 60
8x+12= 60
8x= 48
x= 48:8= 6
b) P= a*h
8* (2x-1)= 56
16x-8=56
16x= 64
x= 64:16= 4
zad. 6
a) 2x-1=4x+2
2x-4x= 2+1
-2x=3
x= -1,5
b) 3x+1= 5x+15
3x-5x=15-1
-2x=14
x= -7
zad. 7
2x+2+6=8-12x-4
2x+12x= 4-8
14 x= -4
x= -4/14= -2/7
zad. 8
sprawdzam dla 2
3(2+1)-2=4*2+5
6+3-2= 8+5
7=13
odp. nie
sprawdzam dla -4
3(-4+1)-2= 4*(-4)+5
-12+3-2= -16+5
-11= -11
Tą liczbą jest -4
Szczegółowe wyjaśnienie: